Modelling of fatigue damage evolution in composite multilayered cylindrical shells. (2016) - Muc, Aleksander; Bondyra, Agnieszka; Miarka, Stanisław
This work presents modelling and numerical analysis of shells with axisymmetric or embedded elliptic delaminations. Numerical studies are conducted including cyclic buckling, contact problems in the post-buckling range and optimisation problems associated with searching from the minimum of the crack growth per one cycle. Finally, the fatigue life is estimated with the use of the fuzzy set approach.